Kalyāṇa-mitta: Professor Hajime Nakamura felicitation volume - Jha, Vashishtha N.; Nakamura, Hajime (Bibliotheca Indo-Buddhica series, 1991)
Contributed articles, chiefly on Buddhism, and Buddhist and oriental philosophy